2013
DOI: 10.1149/2.002312jes
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalysis during Electroless Copper Deposition using Glyoxylic Acid as Reducing Agent

Abstract: Interactions between the cathodic and anodic processes during electroless Cu deposition using glyoxylic acid reducing agent are studied. It is shown that application of the mixed potential theory by decoupling the anodic and cathodic processes leads to erroneous predictions of the electroless deposition rate and the surface mixed potential observed in this electroless system. Chronoamperometry under various conditions of bath composition, electrode surface preparation and applied potential provides evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…3,4 As the above discussion shows in this article, UPD H(ads) is not stable on Cu(111) and as a concentration builds up recombination to form H 2 (g) should be facile. The removal of H(ads) may also be necessary for electroless Cu deposition to proceed.…”
Section: Electochemical Deposition Of H(ads) On Cu(111) and H 2 Evolumentioning
confidence: 80%
“…3,4 As the above discussion shows in this article, UPD H(ads) is not stable on Cu(111) and as a concentration builds up recombination to form H 2 (g) should be facile. The removal of H(ads) may also be necessary for electroless Cu deposition to proceed.…”
Section: Electochemical Deposition Of H(ads) On Cu(111) and H 2 Evolumentioning
confidence: 80%
“…Another candidate of reducing agent for the self-catalytic reaction of Cu is glyoxylic acid. [21][22][23][24][25] Yu et al reported on the anodic oxidation of glyoxylic acid on Cu. 22 In addition, in our previous study, it was clarified that glyoxylic acid can show anodic oxidation on both Cu and Ru.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25] Yu et al reported on the anodic oxidation of glyoxylic acid on Cu. 22 In addition, in our previous study, it was clarified that glyoxylic acid can show anodic oxidation on both Cu and Ru. 26 Figure 1 shows linear sweep voltammograms of glyoxylic acid and formaldehyde for a 30 nm Co liner.…”
Section: Resultsmentioning
confidence: 99%
“…Electroless Cu plating is used in the electronics industry to obtain conductive layers on bare resins [1][2][3]. High-end applications like plating of integrated circuit (IC) substrate interconnects require finegrained copper to achieve small structures [4].…”
Section: Introductionmentioning
confidence: 99%